Percurso funcional da modalização em artigos científicos - Barbosa, Jackson Cícero França (2018)
This research, as well as the postulates of linguistic functionalism, verifies the language in its function to aid communication, observing the motivations that exert influence on the linguistic structures. In this field of observation, we investigate the phenomenon of modalization, in a trajectory that starts from the consideration of this phenomenon as a semantic-pragmatic category related to the way the enunciator is involved with what is said, or with the states of things described (LYONS, 1977; NARROG, 2012; PALMER, 1986, 2001), to the conception, from the functional point of view, of a "grammaticalization of the attitudes and opinions of the speakers" (OLIVEIRA, 2003, p. 245). We investigate the modality in the writing of scientific articles published in annals of academic events, tracing a course of the linguistic mechanisms that express the modalization in this specific genre, aiming to verify if they constitute distinct discursive strategies of argumentation, in light of the functionalist assumptions. The corpus was constituted with samples of ten articles of the areas of pedagogy and ten of engineering. As we believe that this is linked to academic discourse, our research also investigates mechanisms of persuasion conferred by the use of modalities, starting from the hypothesis that these (and the modalizers that express them) have valuable argumentative use in the construction of the scientific article genre, contributing to the convincing and persuasion of the reader of the text regarding the ideas exposed. The theoretical framework that led us to make reflections is anchored in the studies of Givón (1979, 1983, 1984), Croft (1990, 2001), Hopper and Traugott (1991), Neves (1994, 2004, 2011, 2013), Gonçalves (2007), among others. We have identified that some structures specialize in some modality cases despite continuing to perform their primary functions. We attest, based on what the data reveal, that there is regular use of the epistemic modality. In proposing his analysis, in the part of the development of the superstructure of the scientific article, the intention of the author is to prove the veracity of his research, and thus gain authority. To do so, it is used certainty in a large percentage, and at the same time, in a strategic attitude, it leaves the doubt, through the modifying adverbs and the epistemic modalities of certainty combined with the alethic of possibility, in order to gain the adherence of the reader in relation to what it says.